2020
DOI: 10.1534/genetics.120.303149
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microbial Growth Traits Under Serial Dilution

Abstract: Selection of mutants in a microbial population depends on multiple cellular traits. In serial-dilution evolution experiments, three key traits are the lag time when transitioning from starvation to growth, the exponential growth rate, and the yield (number of cells per unit resource). Here, we investigate how these traits evolve in laboratory evolution experiments using a minimal model of population dynamics, where the only interaction between cells is competition for a single limiting resource. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Testing this would require a distribution of K and g max measurements over a large mutant library in a single environment, which to our knowledge has not been done. However, even in the absence of an underlying correlation in mutation effects, such a tradeoff could still emerge across clones within a rapidly evolving population, at least transiently [75, 76]. Experiments with soil bacteria, designed by Velicer et al [77] to evolve a tradeoff in acid degradation, found that lineages adapting for 500 generations in a low concentration environment also become superior competitors in high concentrations and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing this would require a distribution of K and g max measurements over a large mutant library in a single environment, which to our knowledge has not been done. However, even in the absence of an underlying correlation in mutation effects, such a tradeoff could still emerge across clones within a rapidly evolving population, at least transiently [75, 76]. Experiments with soil bacteria, designed by Velicer et al [77] to evolve a tradeoff in acid degradation, found that lineages adapting for 500 generations in a low concentration environment also become superior competitors in high concentrations and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…The factor D is known as the dilution factor and is the ratio of the total biomass at the end of the previous growth cycle (, where is the effective population yield; see Table S2 and Supplementary Information Sec. S3) and the total biomass at the beginning of the next growth cycle ( N 0 ) [76]: This constraint establishes the two possible protocols of serial transfers: either fixing the biomass bottleneck size N 0 (Fig. 3B, top panel) or fixing the dilution factor D (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…of preexisting mutants. It would be interesting both theoretically and experimentally to consider longer evolutionary trajectories [58], and to include de novo mutants, which may appear at any time during the growth phase [59][60][61][62][63][64]. Further extensions include addressing environmental gradients [65][66][67][68], changing environments [69][70][71][72][73][74][75], possible deme extinctions [11], cooperative interactions [76][77][78], and connecting to models of expanding populations [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Populations in our experiments were propagated using growth-dilution cycles, as commonly done in many evolution experiments 46 . In such a scenario, mutations that arise early in the cycle have a higher fixation probability 47 , and mutations that give benefit at the end of the cycle by increasing yield are not directly under selection 48 . At the beginning of each cycle, cell-densities are low and selection forces that depend on biotic interaction are likely only significant after cultures reach high densities toward the end of the cycle.…”
Section: Discussionmentioning
confidence: 99%